2003
DOI: 10.1002/etc.5620220529
|View full text |Cite
|
Sign up to set email alerts
|

Using a freshwater amphipod in situ bioassay as a sensitive tool to detect pesticide effects in the field

Abstract: In situ testing represents an alternative to conventional laboratory toxicity testing of field samples. Juvenile Paramelita nigroculus (Crustacea: Amphipoda) were exposed in situ in two rivers downstream of fruit orchard areas in the Western Cape, South Africa. Exposure took place during six time intervals (3-7 d), of which three represented the first rainfall-induced edge-of-field runoff events of the wet season, which was about two months after the last pesticide application. Survival rates were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…Kirby‐Smith et al (1989) found no effects in field‐deployed shrimp ( P. pugio ) at concentrations below the laboratory effects levels. Chironomids and an indigenous amphipod species ( Paramelita nigroculus ) were established as in situ exposure bioassays for the assessment of aqueous‐phase and particle‐associated insecticide (azinphos‐methyl, chlorpyrifos, endosulfan) toxicity in orchard rivers in the Western Cape of South Africa (Moore et al, 2002; Schulz and Peall, 2001; Schulz et al, 2001c; Schulz, 2003). The response of crayfish ( Procambarus spp.)…”
Section: Effectsmentioning
confidence: 99%
“…Kirby‐Smith et al (1989) found no effects in field‐deployed shrimp ( P. pugio ) at concentrations below the laboratory effects levels. Chironomids and an indigenous amphipod species ( Paramelita nigroculus ) were established as in situ exposure bioassays for the assessment of aqueous‐phase and particle‐associated insecticide (azinphos‐methyl, chlorpyrifos, endosulfan) toxicity in orchard rivers in the Western Cape of South Africa (Moore et al, 2002; Schulz and Peall, 2001; Schulz et al, 2001c; Schulz, 2003). The response of crayfish ( Procambarus spp.)…”
Section: Effectsmentioning
confidence: 99%
“…In situ bioassays can achieve more realistic exposures than laboratory experiments by integrating complex, site-specific conditions [1]. Because of this, in situ bioassays have been used to assess the toxicity of both surface water [2][3][4][5][6][7] and sediment environments [8][9][10]. Some studies have assessed both exposure routes, but did not use the same test species [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, Jergentz et al exposed Hyalella curvispina for 6 d to 8 d in situ to agriculturally contaminated streams and observed mortality in caged amphipods associated with chlorpyrifos measured in suspended particles. In a similar study, in situ exposures with amphipods ( Paramelita nigroculus ) were conducted for 3 d to 7 d in rivers downstream of fruit orchards in South Africa, and significant decreases in survival during runoff events were associated with insecticides (chlorpyrifos, azinphos methyl, endosulfan, and prothiofos) in water and suspended particles . The results of these studies demonstrate that in situ exposures are robust and effective methods of examining the impacts of pesticides on aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, data are not available for organic contaminants (e.g., PAHs, PCBs) in Twenty Mile Creek and Spencer Creek, and thus the contributions of these chemicals to in situ survival cannot be assessed in the present study. Fourth, and lastly, contaminants may have been associated with suspended particles entering the cages [37][38][39] and caused toxicity to caged amphipods, but contaminant analysis of suspended particles was not part of the present study design. In addition, several water quality parameters, such as flow, dissolved oxygen, temperature, TSS, and conductivity, may covary with pesticide inputs and thus impact in situ effects and complicate identification of the causes of toxicity [8].…”
Section: Discussionmentioning
confidence: 99%